Conditioned medium derived from mesenchymal stem cells and spinal cord injury: A review of the current therapeutic capacities - Gholam Reza Kaka; Farrokh Modarresi (IBRO Neuroscience Reports)
Spinal cord injury (SCI) is a debilitating condition of the nervous system that imposes considerable challenges for subjects, such as bladder and bowel incontinence and infections. The standard therapeutic strategy is methylprednisolone utilization accompanied by surgical decompression. However, achieving an effective therapy with the minimum side effects for SCI is still a puzzle. Nowadays, mesenchymal stem cell (MSC) therapy has received much consideration in scientific communities in light of its pharmacological and therapeutic properties, for instance, anti-inflammatory, regenerative, analgesic, and immunomodulatory influences. Despite the mentioned advantages for MSCs, their tumorigenic potential is a limiting agent for its wide therapeutic application. Recent documents show that the use of conditioned medium (CM) derived from MSCs can largely solve these problems. CM encompasses neuroprotective growth factors and cytokines, such as stem cell factor (SCF), vascular endothelial growth factor (VEGF), and glial cell line-derived neurotrophic factor (GDNF). The persuasive evidence from experimental studies revealed that CM originating from MSCs can have a considerable role in the amelioration of SCI. Hence, in the current papers, we will review and summarize evidence indicating the anti-SCI mechanisms of MSC-derived CM by relying the current experimental data.